Targeting thymidine phosphorylase as a potential therapy for bone loss associated with periprosthetic osteolysis - Gen Matsumae; Tomohiro Shimizu; Yuan Tian; Daisuke Takahashi; Taku Ebata; Hend Alhasan; Shunichi Yokota; Ken Kadoya; Mohamad Alaa Terkawi; Norimasa Iwasaki (Wiley, 2021)
Abstract Macrophages are generally thought to play a key role in the pathogenesis of aseptic loosening through initiating periprosthetic inflammation and pathological bone resorption. The aim of this study was to identify macrophage‐derived factors that promote osteoclast differentiation and periprosthetic bone destruction. To achieve this, we examined the effects of 12 macrophage‐derived factors that were identified by RNA‐seq analysis of stimulated macrophages on osteoclast differentiation. Surprisingly, thymidine phosphorylase (TYMP) was found to trigger significant number of osteoclasts that exhibited resorbing activities on dentine slices. Functionally, TYMP knockdown reduced the number of osteoclasts in macrophages that had been stimulated with polyethylene debris. TYMP were detected in serum and synovial tissues of patients that had been diagnosed with aseptic loosening. Moreover, the administration of TYMP onto calvariae of mice induced pathological bone resorption that was accompanied by an excessive infiltration of inflammatory cells and osteoclasts. The RNA‐seq for TYMP‐induced‐osteoclasts was then performed in an effort to understand action mode of TYMP. TYMP stimulation appeared to activate the tyrosine kinase FYN signaling associated with osteoclast formation. Oral administration of saracatinib, a FYN kinase inhibitor, significantly suppressed formation of bone osteolytic lesions in a polyethylene debris‐induced osteolysis model. Our findings highlight a novel molecular target for therapeutic intervention in periprosthetic osteolysis.